Skill development practice-related challenges, and associated factors among nursing students - Bizuayehu Atinafu Ataro; Almaz Addisie; Temesgen Geta Hardido; Getachew Nigussie Bolado; Dawit Simeon Bilate; Yakob Lencha Leka; Beskut Bezabih (BMC, 2024)
Abstract Background Nurse students reportedly face lots of challenges during skill development practice in health institutions. However, the prevalence of challenges and factors associated aren't well understood yet. Objective The objective of the study was to identify the challenges experienced by nursing students in health institutions during skill development practice. Method A cross-sectional study was employed on the participants selected using a simple random sampling technique. The data was cleaned using Epi-data and exported to SPSS for analysis. Logistic regression analysis and correlation analysis were carried out to identify the associated factors. Result The participants are more challenged by instructor factors (43.6%) and facility factors (40%). The prevalence of the challenge was 16.9%. Substance use and learning institutions are found to be independent predictors. A negative correlation was identified between the total challenge score and the overall competency score. Conclusion The determined nursing students' challenges are strong enough to affect the quality of education; therefore, it is essential to plan and improve the students' integrated supportive supervision.